Mitochondria-targeted nanoparticles for heart failure therapy: Rational design and therapeutic mechanisms - Qiuyue Song; Kang Fang; Xinhai Cui; Wenli Xie; Jie Zhao; Xianjun Fu; Kuo Xu (Chemical Engineering Journal, 2026)

Chemo-mechanically regulated single-crystal Ni-rich layered cathodes for all-solid-state lithium batteries - Haonan Zheng; Chaoyi Chen; Xi Zhang; Xianjun Zhu; Jiaxing Xie; Kunxiang Liu; Zhaoyu Zhai; Zhikai Zhou; Shuangying Wei; Bing Wu; Zdeněk Sofer; Yanqing Fu; et al. (Chemical Engineering Journal, 2026)

Medicinal seahorses (Hippocampus spp.) for Alzheimer’s disease within species conservation framework: an integrated review of ethnopharmacology, bioactivity, bibliometrics, and network pharmacology - Peng Song; Mengyu Wang; Tao Liu; Zhuoqing Zhang; Xia Ren; Yao Liu; Jerome P. L. Ng; Vincent Kam Wai Wong; Betty Yuen Kwan Law; Xianjun Fu; Liqun Qu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Three new methylene-bridged bisflavonoid glycosides with cardioprotective activity from Suaeda glauca - Xianrui Ding; Jia Jia; Xianjun Fu; Zhengwei Gu; Kuo Xu (Phytochemistry Letters, 2025)

Unveiling the ∼110 Ma continental arc in South China: geochemical and isotopic insights from offshore magmatic records in the East China Sea Basin - Lichen Hu; Ning Li; Xiaowei Fu; Xianjun Tang; Kailong Feng; Weilin Zhu; Xi Xu (Gondwana Research, 2025)

Marine octopus: global distribution, extraction methods, bioactive biomaterials, and biomedical applications - Mengfei Li; Zhihong Deng; Kun Cheng; Xianjun Fu; Xiuxue Li (Frontiers in Marine Science, 2025)
Octopus, an abundant marine species with diverse applications, is attracting growing attention for its unique biological characteristics and potential utilization in food science and biotechnology. Octopus contain amino acids, active peptides, fatty acids and trace elements and these bioactives exhibit a wide range of effects, including anti-bacterial, anti-tumor, antioxidant and anti-aging activities. The structure of octopus arm and suckers provides biomimetic design inspiration for tissue engineering and the regenerative ability of octopus provides reference for research in biomedical material. Therefore, this review systematically summarizes the research progress on octopus resource distribution, extraction methods, nutrients, bioactive compounds substances and research on regeneration material, aiming to promote the development and utilization of octopus resources. Firstly, the extractions methods of octopus were systematically reviewed. Secondly, seven kinds of nutrients concluded were introduced to reveal the nutritional components of octopus. Finally, the application of octopus in biotechnology and the research progress on their regenerative ability were summarized. This review provides a basis and reference for octopus functional nutrients and application of octopus biomedical materials.

Differential geological responses and geodynamic mechanisms of major Cenozoic tectonic Movements in the East China Sea Shelf basin - Yiming Jiang; Xianjun Tang; Xiaowei Fu; Rongquan Zhong; Weilin Zhu (Journal of Asian Earth Sciences, 2025)

Individual traits modify environmental effects on interaction, connectivity, and productivity of macrophyte community - Hui Fu; Jingjing Guo; Xianjun He; Yaoqi Chen; Zhouhang Wu; Yili Ge; Guojun Cai (Hydrobiologia, 2024)

Hybrid nanovesicles comprising induced pluripotent stem cells and dendritic cell-derived exosomes enhance antitumor immunity - Ronghao Wang; Xianjun Li; Guining Fu; Mingyuan Hu; Haozhao Dou; Guihong Zhang; Qilin Pengshun; Jianfeng Mao; Tianchuan Zhu; Qingdong Cao (Chemical Engineering Journal, 2024)

Tanshinone IIA, originated from Salvia miltiorrhiza, activated EPO/EPOR-JAK2-STAT5 pathway in rat blood deficiency therapy - Miao Wang; Zhihong Deng; Congwei Shi; Kun Cheng; Runxiang Zhai; Xiuxue Li; Xianjun Fu (South African Journal of Botany, 2024)

Identification of important gene signatures in schizophrenia through feature fusion and genetic algorithm - Zhixiong Chen; Ruiquan Ge; Changmiao Wang; Ahmed Elazab; Xianjun Fu; Wenwen Min; Feiwei Qin; Gangyong Jia; Xiaopeng Fan (Mammalian Genome, 2024)

Methylseleninic acid inhibits human glioma growth in vitro and in vivo by triggering ROS-dependent oxidative damage and apoptosis - Wang Chen; Pida Hao; Qile Song; Xiaotong Feng; Xuan Zhao; Jincheng Wu; Zixiang Gong; Jinli Zhang; Xiaoyan Fu; Xianjun Wang (Metabolic Brain Disease, 2024)

A review on distribution, biogeochemistry of antimony in water and its environmental risk - Xinxin Fu; Xianjun Xie; Laurent Charlet; Jing He (Journal of Hydrology, 2023)

Discovery of natural polyphenols from the wild vegetable Suaeda salsa L. with potential cardioprotective functions - Kuo Xu; Xinhai Cui; Xia Ren; Jie Meng; Xianjun Fu; Qing Xia (Food Chemistry, 2023)

Advances in the Global Distribution, Chemical Constituents, and Pharmacology of Hippocampus, a Traditional Marine Chinese Medicine - Xinhai Cui; Xiangfeng Zhao; Jintong Li; Ziwei Li; Xia Ren; Yangang Zhao; Xianjun Fu; Xiuxue Li (Frontiers in Marine Science, 2021)
Hippocampus is an important traditional marine Chinese medicinal resource that has been used to warm and tonify kidney yang in the clinic for a long time in China. Modern pharmacological studies show that its active ingredients display a wide range of pharmacological activities associated with the kidney, such as anti-inflammation, antioxidation, antitumor, and neuroprotective effects. Herein, we systematically summarize and analyze the research progress on the resource distribution, active ingredients, pharmacological activities, and clinical application of Hippocampus . First, the species and worldwide distribution of Hippocampus were assessed to clarify the existing resources, and the results showed that 44 species of Hippocampus have been found in 159 countries and regions worldwide. Then, based on the analysis of 16 kinds of active ingredients and extraction methods, the relationship between the ingredient extraction and pharmacological activities of Hippocampus was revealed. This review may provide a foundation for further research on the potential active ingredients and mechanisms of Hippocampus . In addition, the research status of traditional prescriptions containing Hippocampus was evaluated. The results implied that research on Hippocampus is still in its infancy, and the mechanism and material basis of its efficacy have not been clarified. This paper should provide directions for further studies on Hippocampus .

Identification of a novel mutant spp1 that specifies the identity of inflorescence meristem in rice - Peizhou Xu; Asif Ali; Yun Li; Hongyu Zhang; Xiaoqiong Chen; Shaohong Fu; Yang Jin; Zhongwei Zhang; Shu Yuan; Xianjun Wu (Plant Biosystems, 2020)

Effect of male sterile and fertile cytoplasm on nuclear DNA methylation in hybrid rice - Asif Ali; Yun Li; Hui Chen; Peizhou Xu; Hongyu Zhang; Xiaoqiong Chen; Liao Yongxiang; Shaohong Fu; Tingkai Wu; Muhammad Zafar Iqbal; Muhammad Umer Farooq; Xianjun Wu (Acta Physiologiae Plantarum, 2019)

Cyanidin-3-O-glucoside Induces Apoptosis and Inhibits Migration of Tumor Necrosis Factor-α-Treated Rat Aortic Smooth Muscle Cells - Xuerui Yan; Lin Wu; Bin Li; Xianjun Meng; Hanping Dai; Yanan Zheng; Junfan Fu (Cardiovascular Toxicology, 2016)

Genetic mapping of a QTL controlling leaf width and grain number in rice - Yonghang Tian; Hongyu Zhang; Peizhou Xu; Xiaoqiong Chen; Yongxiang Liao; Baolin Han; Xiangbin Chen; Xiangdong Fu; Xianjun Wu (Euphytica, 2015)

Genetic characterization of a new cytoplasmic male sterility system (hau) in Brassica juncea and its transfer to B. napus - Zhengjie Wan; Bing Jing; Jinxing Tu; Caozhi Ma; Jinxiong Shen; Bin Yi; Jing Wen; Tao Huang; Xianjun Wang; Tingdong Fu (Theoretical and Applied Genetics, 2008)